Government Intervention and Bank Market Power : Lessons from the Global Financial Crisis for the COVID-19 Crisis. (IMF Working Papers; Working Paper, 2020)
The COVID-19 pandemic could result in large government interventions in the banking industry. To shed light on the possible consequences on market power, we rely on the experience of the global financial crisis and exploit granular data on government interventions in more than 800 banks across 27 countries between 2007 and 2017. For identification, we use a multivariate matching method. We find that intervened banks experience a significant decline in market power with respect to matched non-intervened banks. This effect is more pronounced for larger and longer interventions and is driven by a rise in costs-mostly because of higher loan impairment charges-which is not followed by a similar increase in prices.